Substitution, Risk Aversion, and the Temporal Behavior of Consumption and Asset Returns: A Theoretical Framework - Epstein, Larry G.; Zin, Stanley E. (Econometrica, 1989)
Larry G. Epstein, Stanley E. Zin, Substitution, Risk Aversion, and the Temporal Behavior of Consumption and Asset Returns: A Theoretical Framework, Econometrica, Vol. 57, No. 4 (Jul., 1989), pp. 937-969